Pengaruh Kepemilikan Manajerial Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Yamashita; Yudha, Agam Mei; Dewi, Rindy Citra; Saputra, Deni (Journal of Science Education and Management Business, 2022)
This study aims to determine how much influence Managerial Ownership and Company Growth have on Firm Value with Institutional Ownership as a Moderating Variable (In Manufacturing Companies listed on the Indonesia Stock Exchange for the 2016-2020 period). From this research, the following conclusions are obtained: (1) There is a significant influence between Managerial Ownership on Company Value. (2) There is a significant influence between the growth of the company on the value of the company. (3) There is a significant influence between Managerial Ownership and Company Growth on Firm Value. (4) Managerial ownership partially has a significant effect on firm value with institutional ownership as a moderating variable. (5) Company growth partially has no significant effect on firm value with institutional ownership as a moderating variable in the company (6) managerial ownership and company growth partially significant effect on firm value with institutional ownership as a moderating variable